Prevalence of dry eye in patients with systemic lupus erythematosus: a meta-analysis - Yan Xie; Lixiang Wang; Yingping Deng (BMJ Open)
Objectives To investigate dry eye disease (DED) in patients affected by systemic lupus erythematosus (SLE).Methods We conducted a systematic search of the literature on PubMed, EMBASE and the Cochrane Library databases from conception to 30 April 2020 for studies related to dry eye, secondary Sjögren’s syndrome (sSS) and SLE. Original full-text articles with the number of patients diagnosed with SLE of over 15 were included. The risk of bias was evaluated with a validated critical appraisal tool which assessed study quality based on confounding factors, selection bias, bias related to measurement and bias related to data analysis. Data were extracted and pooled to evaluate the overall prevalence of DED with the random-effect model and sSS with the fixed effect model.Results A total of 29 studies were included and 18 273 participants were involved. The pooled data showed that the overall prevalence of DED was 16% (95% CI 10% to 21%, p<0.001) in patients of SLE. Dry eye symptoms and abnormal Schirmer’s test were found in 26% (95% CI 20% to 32%, p<0.001) and 24% (95% CI 14% to 34%, p<0.001) of patients with SLE, respectively. 12% (95% CI 9% to 15%, p<0.001) of patients also met the criteria of sSS. The OR of DED in patients with SLE was 4.26 (95% CI 3.47 to 5.05, p<0.001) compared with healthy controls. The meta-regression analysis showed that the sample size (p=0.004) and study location (p=0.022) could be the source of heterogeneity.Conclusions DED and sSS are both common in patients with SLE.